1984
DOI: 10.1159/000172920
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Inhibits Renal Functional Adaptation to Nephron Loss

Abstract: Immediately after unilateral nephrectomy, the glomerular filtration rate (GFR) and urinary excretion rate increase in the remaining transplanted rat kidney. In a previous study, we found that GFR in a transplanted kidney was reduced through an activation of the tubuloglomerular feedback control. Excision of the rat’s own remnant kidney then reduced feedback sensitivity and thereby allowed GFR to rise. The present study aimed at investigating whether prostaglandins are involved in this functional adaptation. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
(10 reference statements)
1
17
0
Order By: Relevance
“…This phenomenon has been demonstrated by other authors in chronic situations such as two-kidney, one-clip Goldblatt hypertensive rats, unilateral nephrectomy and trans planted kidneys [Hahne et al" 1984]. Very little attention has been paid to study the functional alteration in the contralateral kid ney to acute unilateral renal arterial constric tion [Murray et al.…”
Section: Discussionmentioning
confidence: 85%
“…This phenomenon has been demonstrated by other authors in chronic situations such as two-kidney, one-clip Goldblatt hypertensive rats, unilateral nephrectomy and trans planted kidneys [Hahne et al" 1984]. Very little attention has been paid to study the functional alteration in the contralateral kid ney to acute unilateral renal arterial constric tion [Murray et al.…”
Section: Discussionmentioning
confidence: 85%
“…These data suggested that prostaglandins (E2 or '2) have a permissive role in the tubuloglomerular feed-back mechanism but are probably not the mediator of the response. In contrast, Hahne et al (1984) reported that indomethacin did not affect tubuloglomerular feed-back in the rat and Boberg et al (1984) and Persson, Hahne & Selen (1983) reported that PGI2 reduced the sensitivity of the tubuloglomerular feed-back in the rat kidney. However, Persson et al (1983) found that PGE2 and 193+52 770+187 * * C is the measurement at the control point.…”
Section: Resultsmentioning
confidence: 93%
“…Likewise, the response is blunted, but not abolished, by blockade of cyclooxygenase with indomethacin (indo) or meclofenamate (4)(5)(6). Simultaneous blockade of AII generation and PG production with captopril and meclofenamate abolishes TGF-induced changes in glomerular capillary hydrostatic pressure although some changes in single nephron GFR (SNGFR) persist (7l).…”
Section: Introductionmentioning
confidence: 99%
“…Indo inhibits cyclooxygenase and reduces the production of all PGs including PGI2 and TX (4,6,7). Indo (2.5 mg -ml-', Sigma Chemical Co.) was dissolved in 1 M Na2CO3 solution and given to group 2 rats to assess the effects of nonselective inhibition of production ofboth vasodilator and vasoconstrictor PGs on the TGF response.…”
Section: Introductionmentioning
confidence: 99%